Exploring the Multifaceted Humor Function of Dark Humor in Trevor Noahs Show Son of Patricia - Shabrina, Annisa Nurul; Ain, Qurat ul; Pratama, Hendi (Allure Journal, 2024)
The objective of this study was to gain insight into Trevor Noah's intention for employing dark humor through applying Attardo's humor function framework to his stand-up comedy performance "Son of Patricia. This qualitative research utilized a phenomenological methodology. The investigation aimed to explore the phenomenon of dark humor based on Trevor Noah's personal experiences as conveyed in his act. The study analyzed dark humor found in Trevor Noah's stand-up show "Son of Patricia" through the lens of Attardo's (1994) humor functions. The result showed that the frequent humor function found was defunctionalisation for amusement and the jokes often involve playing with the language followed with social management, decommitment and mediation. Exploring the multifaceted humor function of dark humor in Trevor Noah's show "Son of Patricia" revealed a nuanced and thought-provoking approach to comedy. Noah skillfully employed dark humor as a tool for social management, shedding light on sensitive issues such as race, politics, and societal norms. While dark humor can be polarizing, Trevor Noah demonstrates its potential to be a powerful vehicle for social commentary and awareness.